[Rezension von: Stanton, Graham, 1940-2009, Studies in Matthew and early Christianity] - Eve, Eric (The journal of theological studies, 2014)
This volume comprises a collection of 26 essays (25 of which have been previously published elsewhere between 1972 and 2007) by the late British New Testament scholar Graham Stanton. According to the editors, the aim ‘is to offer a coherent selection of writings on what are perhaps Graham Stanton's most prominent contributions to scholarship: the Gospel of Matthew (Part I), other New Testament writings (Part II), and early Jewish-Christian encounters with a special focus on Justin Martyr (Part III)’., The coherence is most apparent in Part I, where the focus is on a single gospel.